Construction of N-loaded conjugated polymer for highly effective removal of iodine in organic solution. Issue 1 (February 2023) - Zheng, Qian; Huang, Bingyuan; Du, Xueying; Zhang, Juan; Fu, Hongquan; Gao, Hejun; Liao, Yunwen
Abstract: Efficient capture of radioiodine is critical during nuclear fuel reprocessing and nuclear accidents. The development of material with excellent adsorption properties of radioiodine has always been a significant challenge. Three kinds of N-loaded conjugated polymers were prepared using the solvothermal method by changing the N-group in pyrrole. The effect of nitrogen type on the structure of conjugated polymers was investigated by SEM, BET, FT-IR, XPS, and EPR. Despite their low specific surface area, their mesoporous structure is conducive to transporting iodine molecules. The results showed that in the conjugated system, the adsorption capacity of alkyl tertiary amines for iodine was better than that of aminoethyl tertiary amines and secondary amines, and the maximum adsorption capacity could reach 737.4 mg/g. The adsorption mechanism of iodine on N-loaded conjugated polymer is mainly the interaction of charge transfer between iodine and N-aromatic in the organic solution. Highlights: N-loaded conjugated polymers were prepared using the solvothermal method by changing the N-group in pyrrole. NCP were prepared using the solvothermal method. The maximum adsorption capacity of NCP could reach 737.4 mg/g. The adsorption capacity of alkyl tertiary amines for iodine was better than that of aminoethyl tertiary amines and secondary amines.